“Travel and learn adventures” - a business plan for a dignity social enterprise - Tan, Natalie Sook Ling (2021)
This report explains how Dignity for Children Foundation is expanding its education mandate to break the cycle of poverty through quality education, through the set up of an education social enterprise (SE) that delivers travel-and-learn character education programs to a paying audience, namely youth from upper M40 and T20 families, school institutions and corporates. The SE leverages on existing knowledge and core competency of Dignity for developing inclusive education programs. The profits from the SE will fund Dignity’s existing social programs.